Natriuresis induced by cholinergic stimulation of the locus coeruleus in the rat - De Luca, L. A. [UNESP]; Franci, C. R.; Saad, W. A. [UNESP]; Camargo, L. A A [UNESP]; Antunes-Rodrigues, J. (Elsevier, 1990)
Carbachol injected into the locus coeruleus (LC) induced a dose-dependent natriuresis in the rat. This natriuresis was maintained above control levels during the 120 min of urine sampling. Seizures and arterial blood pressure increase were also observed but they disappeared within 20 min after carbachol injection. Natriuresis was not obtained with either injections of carbachol outside the LC or with hypertonic solutions injected into the LC. Injection of atropine into the LC blocked the natriuresis induced by carbachol. In summary, our data show that carbachol induces natriuresis by an action on muscarinic receptors located in the LC region. © 1990.
Keywords: Blood pressure; Carbachol; Cholinergic stimulation; Locus coeruleus; Natriuresis; Seizures; atropine; carbachol; muscarinic receptor; animal cell; animal experiment; blood pressure; intracerebral drug administration; locus ceruleus; male; natriuresis; nonhuman; priority journal; rat; Animal; Blood Pressure; Brain Mapping; Cholinergic Fibers; Locus Coeruleus; Male; Neurons; Potassium; Rats; Rats, Inbred Strains; Receptors, Cholinergic; Support, Non-U.S. Gov't; Water-Electrolyte Balance